2019
DOI: 10.24193/tras.58e.2
|View full text |Cite
|
Sign up to set email alerts
|

"A Community-Based Intervention for Increasing Access to Health Information in Rural Settings"

Abstract: will be held to imply that it contains original unpublished work and is not being submi ed for publication elsewhere at the same time. The language of the journal is Romanian (when the use of diacriticals is required) or an international language (English, French, German, Italian, Spanish, etc.). All submissions must have a title, be 1,5 lines spaced, have a margin of 2 cm all round, be between 7 and 25 pages long, be wri en in Times New Roman Style, have 12 points characters, and must start with an alignment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Fifty-nine included studies were conducted in North America (45%) [ 15 , 17 , 30 , 33 – 35 , 38 , 39 , 42 , 43 , 46 , 49 51 , 54 , 56 , 60 – 62 , 66 , 67 , 69 , 71 , 75 , 76 , 78 , 79 , 82 – 84 , 87 , 88 , 91 , 94 – 96 , 98 105 , 107 , 108 , 114 116 , 118 122 , 124 , 128 , 129 , 136 , 137 ], 18 in Europe (14%) [ 16 , 24 , 26 , 27 , 53 , 57 – 59 , 74 , 77 , 85 , 86 , 111 , 113 , 117 , 125 , 127 , 142 ], 18 in Asia (14%) [ 19 , 28 , 29 , 48 , 55 , 65 , 68 , 73 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-nine included studies were conducted in North America (45%) [ 15 , 17 , 30 , 33 – 35 , 38 , 39 , 42 , 43 , 46 , 49 51 , 54 , 56 , 60 – 62 , 66 , 67 , 69 , 71 , 75 , 76 , 78 , 79 , 82 – 84 , 87 , 88 , 91 , 94 – 96 , 98 105 , 107 , 108 , 114 116 , 118 122 , 124 , 128 , 129 , 136 , 137 ], 18 in Europe (14%) [ 16 , 24 , 26 , 27 , 53 , 57 – 59 , 74 , 77 , 85 , 86 , 111 , 113 , 117 , 125 , 127 , 142 ], 18 in Asia (14%) [ 19 , 28 , 29 , 48 , 55 , 65 , 68 , 73 ,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies included other populations (e.g. African American breast cancer survivors [ 95 ], members of public libraries [ 143 ], women in Tanzania [ 126 ] a rural community [ 127 ], students in an ESOL class [ 17 , 28 , 34 , 41 , 47 , 60 , 62 , 67 , 70 , 80 , 83 , 93 , 95 , 106 , 110 , 112 , 113 , 117 , 120 , 123 , 124 , 126 , 127 , 145 ]. Eighteen studies were a sample of the general population [ 16 , 19 , 24 , 43 , 48 , 49 , 56 , 58 , 68 , 73 , 77 , 79 , 81 , 92 , 108 , 121 , 128 , 144 ] and sixteen studies did not identify the population [ 15 , 20 , 21 , 30 , 36 , 71 , 76 , 89 , 98 , 103 , 116 , 118 , 136 , 138 , 140 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…This includes not only targeting potential patients based on their ethnicity, race, language, and immigration status, but also among rural communities and the importance of having rurally based health centers and initiatives. Kunz et al (2017) emphasized the important role practitioners and policy makers play in elevating and addressing the unique needs of rural communities (Blaga et al, 2019). James et al (2017) found that racial and ethnic minority populations in rural areas generally lacked access to health care and had significant health challenges.…”
Section: Health Insurance Eligibility and Affordabilitymentioning
confidence: 99%
“…Currently, mass-media plays various functions in society; providing information, monitoring issues of general interest, social integration and entertainment. The role of the media is adaptive and changing according to the processes occurring throughout Europe [1]. Information about wellness and individual lifestyle choice conveyed to the public through media can influence and facilitate healthy life styles [2] [3].…”
Section: Introductionmentioning
confidence: 99%